A2.08 Extrathymic autoimmune regulator (AIRE) expression can be induced in dendritic cells by CD40-mediated activation of noncanonical NF-κb signalling, but is impaired in primary sjögren's syndrome. (24th February 2016) - Huitema, LFA; Helder, B; Noort, AR; Lebre, MC; Tas, SW
Abstract : Background: The nuclear factor (NF)-κB family of transcription factors has a key role in the regulation of inflammation. We have previously demonstrated that activation of noncanonical NF-κB signalling in dendritic cells (DC) via CD40 stimulation is important for the induction of the immunoregulatory enzyme indoleamine 2, 3-dioxygenase (IDO). This pathway is also involved in the expression of Autoimmune Regulator (AIRE) in the thymus, which is essential central tolerance. Peripheral extrathymic AIRE-expressing cells (mainly antigen presenting cells, including DC) can also induce tolerance. However, stimuli that induce extrathymic AIRE expression in DC are unknown. Therefore, we studied whether activation of noncanonical NF-κB signalling induces AIRE expression in monocyte-derived DC (moDC) and whether this induction is altered in moDC derived from patients with autoimmunity, using primary Sjögren's syndrome (pSS) as a prototypic systemic autoimmune disease. Objective: To study whether activation of noncanonical NF-κB signalling induces AIRE expression in moDC from healthy donors and pSS. Methods: MoDC were generated by culturing monocytes for 6 days with GM-CSF and IL-4. Maturation was induced by addition of the noncanonical NF-κB stimulus anti-CD40 for 48 h. Cleavage of p100 into p52, IDO and AIRE protein was analysed by Western blot. Immunofluorescence staining for RelB was performed on cytospins of moDC. RelB protein was visualised by confocal microscopy. siRNA-mediated silencing of NF-κB-inducing kinase (NIK), the main activating kinase of the noncanonical pathway, was accomplished by neon electroporation. Results: Anti-CD40 stimulation of moDC from healthy donors induced cleavage of p100 and nuclear translocation of RelB, which is indicative of active noncanonical NF-κB signalling. This was accompanied by upregulation of IDO and AIRE expression, which was inhibited by siRNA-mediated silencing of NIK. Anti-CD40 stimulation of moDC derived from pSS patients also resulted in activation of noncanonical NF-κB signalling and upregulation of IDO. However, AIRE expression was to a much lesser extent upregulated in moDC derived from pSS patients compared to healthy donor DC. Conclusion: Extrathymic AIRE expression can be induced in moDC via CD40-stimulation and is regulated by noncanonical NF-κB signalling. This mechanism is impaired in pSS patients. The functional consequences of this potentially defective immunoregulatory program are currently investigated.